Poetry as A Medium of Sufistic Da'wah: Analysis of Abdul Wachid B.S.’s Poetry - Budiantoro, Wahyu (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2019)
The purpose of this study is to identify and reveal that poetry can be used as a medium of Sufistic da'wah. Research method using library research by reviewing poetry Abdul Wachid B.S. in Hyang's rhyme collection. The results of this study are: first, the narrative of mystical love ('isyq) in the acquisition of Abdul Wachhid B.S. as the foundation of sufistic da'wah, secondly, the value of sufistic humanism as a prophetic and universal human representation; third, the image / depiction of nature as a manifestation of the values of hablum min al-alam (relation to the nature). The impact of this research in the context of da'wah science can provide a new dimension, namely the dimension of literature and culture in the practice of Sufi preaching. In addition, Sufism or Sufism literature approach can also enrich the viewpoint of the da'wah practitioners to innovate for good and peace da'wah. Tujuan penelitian ini adalah untuk mengidentifikasi dan mengungkapkan bahwa puisi bisa digunakan sebagai media dakwah sufistik. Metode penelitian menggunakan library research (riset kepustakaan) dengan menelaah puisi-puisi Abdul Wachid B.S. dalam kumpulan sajak Hyang. Hasil dari penelitian ini adalah: pertama, narasi cinta mistik (‘isyq) dalam perpuisian Abdul Wachhid B.S. sebagai dasar dakwah sufistik, kedua, nilai humanisme sufistik sebagai representasi kenabian dan kemanusiaan universal, ketiga, citraan/ penggambaran alam sebagai manifestasi dari nilai-nilai hablum min al-alam. Dampak penelitian ini dalam konteks ilmu dakwah dapat memberikan dimensi baru, yaitu dimensi sastra dan kebudayaan dalam praktik dakwah sufistik. Selain itu, pendekatan sastra sufistik atau tasawuf juga dapat memperkaya sudut pandang para praktisi dakwah untuk melakukan inovasi bagi dakwah yang sehat dan sejuk.